“Othering” Through War: Depiction of Asians/Asian Americans in U.S. History Textbooks - Minju Choi; Li Lucy; Patricia Bromley; David Bamman (Educational Researcher, 2025)
Using computational methods, we investigate a data set of 874,125 sentences from 30 U.S. history textbooks used in California and Texas schools to consider how they discuss Asians/Asian Americans. Only 1% of all sentences in our sample has any mention of Asians. Most of these sentences focus on Chinese and Japanese, and when individuals are named, they are usually White. The most prevalent topics in which Asians appear are about war. Discussions of wars are a centerpiece of history textbooks, but the dominance of such narratives is especially high for Asians relative to other ethno-cultural groups. The sentiment of verbs used to describe Asians is strikingly negative. Asians are described more negatively than others in both war and nonwar contexts.
Keywords: 300; Asian Americans; content analysis; curriculum; history; natural language processing; textbooks